Pengelolaan Sarana dan Prasarana Pendidikan dalam Membangun Sekolah yang Efektif di Sekolah Dasar - Rima Yuni Saputri; Sheren Dwi Oktaria; Muhisom (UNIB Press, 2023)
This research is motivated by problems related to the management of educational facilities and infrastructure that are not optimal. The purpose of this study is to determine how the management of educational facilities and infrastructure to create effective schools in elementary schools. The method used in this research is mix method with sequential explanatory research design. This research uses saturated samples with a population and sample size of 41 people, while the data sources in this study are principals, representatives of teaching staff and education staff. The instruments used in this study were questionnaires, interviews and documentation. The results showed that the management of educational facilities and infrastructure at SDN 2 Rajabasa and SDN 3 Kampung Baru was carried out in three stages, namely the planning stage, the maintenance and supervision stage, and the reporting of educational facilities and infrastructure. while based on quantitative data analysis it can be concluded that there is an influence in the management of educational facilities and infrastructure which is 0.156 or 15% to create effective schools in elementary schools.